2020
DOI: 10.31933/dijemss.v2i2.658
|View full text |Cite
|
Sign up to set email alerts
|

How Price Perception and Trust Affected Millenial Online Buying Interest During Covid-19 Pandemic in West Java

Abstract: The implementation of Work From Home also has an impact on the trend of buying interest online. The trend of buying interest online is usually carried out by young consumers or can be called as millenials because they are the ones who use online facilities to fulfill their needs even though they are not in a Covid-19 condition. Interest in buying online is influenced by price perception and level of consumer trust. Aim of this research for find out the influence of price perceptions and consumer trust on onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 12 publications
(7 reference statements)
2
9
0
Order By: Relevance
“…Consumers are more likely to have trust in platforms that offer prices that align with the value they receive. This finding is consistent with the results of a study conducted by Lutfie and Marcelino [54], which found that price perception significantly affects millennial consumer trust.…”
Section: The Effect Of Price Perception On Consumer Trustsupporting
confidence: 92%
See 4 more Smart Citations
“…Consumers are more likely to have trust in platforms that offer prices that align with the value they receive. This finding is consistent with the results of a study conducted by Lutfie and Marcelino [54], which found that price perception significantly affects millennial consumer trust.…”
Section: The Effect Of Price Perception On Consumer Trustsupporting
confidence: 92%
“…Therefore, price perception not only impacts consumer trust but also influences purchasing decisions. This is supported by the findings of research conducted by Lutfie and Marcelino [54], which demonstrate that price perception has a significant effect on millennial consumer trust. Similarly, Anwar and Andrean [20] discovered a positive and significant relationship between price perception and purchasing decisions.…”
Section: The Effect Of Perceived Price On Trust and Online Purchasing...supporting
confidence: 58%
See 3 more Smart Citations